2011
DOI: 10.2105/ajph.2011.300142
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Consumption of Water in School and Child Care Settings: Access, Challenges, and Strategies for Improvement

Abstract: Children and adolescents are not consuming enough water, instead opting for sugar-sweetened beverages (sodas, sports and energy drinks, milks, coffees, and fruit-flavored drinks with added sugars), 100% fruit juice, and other beverages. Drinking sufficient amounts of water can lead to improved weight status, reduced dental caries, and improved cognition among children and adolescents. Because children spend most of their day at school and in child care, ensuring that safe, potable drinking water is available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…Access varies by region and by the sociodemographic makeup of the student body, 18 and providing adequate access to safe water can be challenging for schools with older infrastructure or limited access to safe tap water sources. 19, 2223 Although a recent, nationally representative survey of U.S. public schools found that most public school students (over 86%) attend schools that meet the HHFKA requirement for providing free water during lunch, 24 this survey relied on reports from school principals, the validity of which are unclear. In order to assess whether public health action is needed to improve water access in schools and thus reduce the potential negative health impacts of inadequate water intake and hydration, there is a need for objectively measured data about the adequacy of water access in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Access varies by region and by the sociodemographic makeup of the student body, 18 and providing adequate access to safe water can be challenging for schools with older infrastructure or limited access to safe tap water sources. 19, 2223 Although a recent, nationally representative survey of U.S. public schools found that most public school students (over 86%) attend schools that meet the HHFKA requirement for providing free water during lunch, 24 this survey relied on reports from school principals, the validity of which are unclear. In order to assess whether public health action is needed to improve water access in schools and thus reduce the potential negative health impacts of inadequate water intake and hydration, there is a need for objectively measured data about the adequacy of water access in schools.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions targeting children's fluid intake frequently focus on the school environment [1,6,7,8]. However, there is evidence that home environment significantly influences eating patterns in young children [9].…”
Section: Introductionmentioning
confidence: 99%
“…Drinking water access may be compromised in schools with older infrastructure 23 or municipal water safety issues. 24 Although schools may opt to provide bottled instead of tap water, this is a less sustainable solution because of the higher costs 25 and the labor required for its distribution 23 ; improving tap water access is therefore an important goal. However, even when students have access to free tap water, they may not drink it 26 ; students often perceive tap water as unsafe or unpalatable 27,28 despite tougher safety standards than bottled water.…”
mentioning
confidence: 99%
“…However, even when students have access to free tap water, they may not drink it 26 ; students often perceive tap water as unsafe or unpalatable 27,28 despite tougher safety standards than bottled water. 25 Improving drinking water access and increasing appeal are essential goals.…”
mentioning
confidence: 99%